The Atmospheric Poetics of Not Belonging: Three Adaptations by Andrei Khrzhanovsky - Rybina, Polina (Transcr(é)ation, 2025)
A Russian animated film director Andrei Khrzhanovsky (b. 1939) has made a highly successful cinematic career spanning more than fifty years (his animation discussed in the monographs and articles of Maureen Furness, Laura Pontieri, Maya Balakirsky Katz, Sergei Kapkov, among others). Khrzhanovsky works in different cel animation techniques (drawn and cut-out animation) and is famous for the adaptation of classic prose and poetry through found images – the authors’ correspondence, diaries and drawings (The Pushkin Cycle, 1975–1987; A Cat and a Half, 2002). Frequently, the found images take the form of visual quotations from European art. In the animated films Glass Harmonica (1968), A Grey-Bearded Lion (1995, an adaptation of Tonino Guerra’s tale) and Long Journey (1997), Khrzhanovsky uses images of Italian art to shape atmospheric effects, which position an artist as “not belonging”. In Glass Harmonica appropriated images of Renaissance and surrealist art help to elaborate on the artist’s political nonconformism: “belonging” refers to the dominant narratives of state-sponsored ideology while “not belonging” (Mikhail Bakhtin’s position outside; Alexei Yurchak’s living ‘vnye’) – to different alternative truths of an outsider.In A Grey-Bearded Lion Khrzhanovsky adapts Tonino Guerra’s tale about an Italian circus, and in Long Journey repurposes auteur cinema images and drawings (Federico Fellini) to comment on other issues of the artistic journey and freedom. While erasing the significance of the political context in a more existential sense, Khrzhanovsky continues to use atmospheric effects to portray an artist as an outsider. This essay delves into different manipulations of the mise-en-scène and the movement, which influence the characters’ and the viewer’s “atmospheric feelings”. Focusing on four criteria from Hermann Schmitz’s “felt-bodily alphabet”, two associated with spaces (filled or empty, condensed or non-condensed) and the other two – with types of movement (centripetal or centrifugal; quite or excited), I will look at the dynamics of atmospheric effects in Khrzhanovsky’s animation that positions an artist as not belonging.